Predicting Employees’ Loyalty through Organizational Justice: The Moderating Role of Union Effectiveness - Florenz Hernandez Jaime, Gabriel; Encabo, Paterson (JPAIR Multidisciplinary Research, 2024)
Encouraging fair management practices can foster positive behaviors among employees, such as loyalty. Previous studies have shown that organizational justice is one of the many key drivers of organizational loyalty. However, most of these studies have been carried out in different countries and in non-unionized organizations, leaving an opportunity to fill a gap in the literature. Guided by the social exchange theory, the present undertaking will narrow the gap by examining the direct influence of organizational justice on organizational loyalty in unionized firms and introduces union effectiveness as a moderator variable to investigate the direction of this relationship. The participants are union members (n = 383) from various manufacturing companies in the third district of NCR, Philippines. Using PLS-SEM, the study found that different domains of organizational justice (procedural, distributive, informational, and interpersonal justice) have a significant and direct impact on organizational loyalty. Furthermore, the study revealed that union effectiveness moderates the direct relationship of procedural, distributive, and informational justice to organizational loyalty. However, union effectiveness does not moderate the relationship between interpersonal justice and organizational loyalty. Research implications and limitations are discussed in this study.